2011
DOI: 10.1186/1471-2458-11-224
|View full text |Cite
|
Sign up to set email alerts
|

Chronic occupational exposure to hexavalent chromium causes DNA damage in electroplating workers

Abstract: BackgroundOccupational exposure to chromium compounds may result in adverse health effects. This study aims to investigate whether low-level hexavalent chromium (Cr(VI)) exposure can cause DNA damage in electroplating workers.Methods157 electroplating workers and 93 control subjects with no history of occupational exposure to chromium were recruited in Hangzhou, China. Chromium levels in erythrocytes were determined by graphite furnace atomic absorption spectrophotometer. DNA damage in peripheral lymphocytes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 38 publications
7
61
1
Order By: Relevance
“…33,34 Moreover, it is reported that Cr(VI) often generates free radicals, which in turn activate O 2 and produce ROS, including hydroxyl radicals, singlet oxygen, superoxide and hydrogen peroxide, 23,35 and consequently lead to DNA damage. 36 In our results, the biochemical alterations were confirmed by the presence of pathomorphological alterations in thyroid glands of rats exposed to K 2 Cr 2 O 7 . These alterations are represented by follicular hyperplasia with large interfollicular spaces, desquamated follicles, and congested interfollicular blood vessels (Table 3 and Figure 2).…”
supporting
confidence: 69%
“…33,34 Moreover, it is reported that Cr(VI) often generates free radicals, which in turn activate O 2 and produce ROS, including hydroxyl radicals, singlet oxygen, superoxide and hydrogen peroxide, 23,35 and consequently lead to DNA damage. 36 In our results, the biochemical alterations were confirmed by the presence of pathomorphological alterations in thyroid glands of rats exposed to K 2 Cr 2 O 7 . These alterations are represented by follicular hyperplasia with large interfollicular spaces, desquamated follicles, and congested interfollicular blood vessels (Table 3 and Figure 2).…”
supporting
confidence: 69%
“…Anti-inflammatory properties of some metal NPs have been indicated suggesting them to pose antiinflammatory effects by down regulation of NF-κB signaling pathway in macrophages (95). However, several studies have shown a major role of ROS in cytotoxicity of nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Cr VI in footwear has been demonstrated several times [4,5]. There is potential danger to human health, because hexavalent chromium (Cr VI) salts are easily absorbed by human skin and can cause bladder, kidney and urinary tract cancer [6,7], regardless of dermatological skin disease, as shown in the figure 5.…”
Section: Kc C a = (6)mentioning
confidence: 99%